2012
DOI: 10.2172/1056989
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective tiered environmental assessment of the Mount Storm Wind Energy Facility, West Virginia,USA

Abstract: Bird and bat fatalities from wind energy projects are an environmental and public concern, with post-construction fatalities sometimes differing from predictions. Siting facilities in this context can be a challenge. In March 2012 the U.S. Fish and Wildlife Service (USFWS) released "Land-based Wind Energy Guidelines" to assess collision fatalities and other potential impacts to species of concern and their habitats to aid in siting and management. The Guidelines recommend a tiered approach for assessing risk t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It is also likely that some species, based simply on life history, primarily collide with turbine poles and rarely collide with blades themselves [6,20,93]. Carcasses of low-flying upland game birds, which are unlikely to ever fly into the rotor zone, have been routinely found during carcass searches [34,[94][95][96][97] and Stokke et al [98] found substantial evidence that willow ptarmigan (Lagopus lagopus) frequently collide with turbine poles in Norway. Further, the distance distribution for willow ptarmigan mirrored ours, showing a high peak directly next to the turbine pole (Fig 3) [98].…”
Section: Differences Between Birds and Batsmentioning
confidence: 99%
“…It is also likely that some species, based simply on life history, primarily collide with turbine poles and rarely collide with blades themselves [6,20,93]. Carcasses of low-flying upland game birds, which are unlikely to ever fly into the rotor zone, have been routinely found during carcass searches [34,[94][95][96][97] and Stokke et al [98] found substantial evidence that willow ptarmigan (Lagopus lagopus) frequently collide with turbine poles in Norway. Further, the distance distribution for willow ptarmigan mirrored ours, showing a high peak directly next to the turbine pole (Fig 3) [98].…”
Section: Differences Between Birds and Batsmentioning
confidence: 99%